Review of the brachypterous, micropterous, and apterous Braconidae of the cyclostome lineage (Hymenoptera: Ichneumonoidea) from the Palearctic Region - Belokobylskij, Sergey A.; Kula, Robert R. (Zootaxa, 2012)
The Palearctic species of Braconidae with brachypterous, micropterous, or apterous modification are discussed. Thefollowing new species are described: Chremylus planispinus Belokobylskij (France, Algeria), Chremylus algecirasusBelokobylskij (Spain), Pambolus erogolus Belokobylskij (Mongolia), Pambolus ovchinnikovi Belokobylskij (Kyr-gyzstan), Hormius stauropolicus Belokobylskij (Russia (North Caucasus)), Bracon (Habrobracon) barbieriBelokobylskij (Algeria), and Panerema kamtshatica Belokobylskij (Russia (Kamchatka)). The following species are re-described: Heterospilus hemipterus (Thomson) (male and female), Chremylus pomonellae (Atanasov) (male, female andmacropterous form), Hormius minialatus Tobias (female), and Aleiodes (Chelonorhogas) hemipterus Marshall (male andfemale). Lituania brachyptera Jakimavicius, 1968 is a new synonym of Eurybolus hemipterus Thomson, 1892. Chremyluspomonellae (Atanasov), new combination, is transferred from Rhyssalus. Aleiodes hemipterus is placed in the subgenusChelonorhogas Enderlein. Asobara subalata (Zaykov & Fischer) is returned from Phaenocarpa Foerster. New distribu-tion records are reported for Ecphylus (Sactopus) caudatus Ruschka, H. hemipterus, Rhaconotus hispanicus Belokobyl-skij, Pambolus tricolor (Ruthe), Hormius minialatus Tobias, A. (C.) hemipterus, and Pseudopezomachus kasparyaniTobias. A key for identifying all Palearctic flightless cyclostome braconid species, and the genera in which they are placed,is provided. A discussion about the diversity, morphological characters, and natural history of wing size reduction, and possible reasons for flightlessness, is provided.